ANALISIS HUKUM TERHADAP PELAKU PELECEHAN SEKSUAL YANG DILAKUKAN ATASAN DALAM LINGKUP KERJA (Studi Kasus Putusan Nomor148/Pid.B/2018/PN Lbh) - Stefanus, Stefanus; Hary Soeskandhi (JISOS: JURNAL ILMU SOSIAL, 2022)
There are 2 types of sexual harassment acts, namely verbal harassment through speech and non-verbal through direct action, the problem of this harassment occurs in a complex manner and has a fatal impact on the victim because it can cause anxiety and unrest in the community, this act of harassment does not just happen but is a habit. What the perpetrators do is considered normal, every worker has the right to get protection which has been stated in Law No. 13 of 2003 concerning Manpower, namely the right to safety and health at work as well as morals, decency and treatment with good dignity. This study uses a normative method with 2 (two) approaches, namely the statutory and conceptual approach by reviewing library materials in order to answer the issues at hand. The results of the study, namely imposing a prison sentence of 5 (five) years on the perpetrator will not cause a deterrent effect and do not provide a sense of justice for the victim and the victim's family, the good name of the civil service police unit, the panel of judges should impose a sentence by guaranteeing justice, certainty and truth. for society.